PENILAIAN KINERJA BERDASARKAN KONSEP VALUE FOR MONEY UNTUK PENERIMAAN PAJAK HOTEL DAN RESTORAN - Yasa, I Made Mara; Jati, I Ketut (E-Jurnal Akuntansi, 2017)
Rate the performance of the Department of Revenue Buleleng  important to assess the accountability of the organization. Accountability here is showing how funds are spent, but includes the ability mununjukkan how funds are spent economically, efficiency, and effectiveness. The purpose of this study is to determine the performance of the Department of Revenue on receipt of Buleleng Regency Hotel and Restaurant Tax. The data used in this research is secondary data. Based on the results of the analysis showed that the performance of the Department of Revenue Buleleng, seen from the economic rationale for acceptance Hotel and Restaurant Tax for the years of 2012 and 2013 that ratio is very economical, in 2010 the ratio is quite economical, 2009 and 2011 the ratio is economical. Judging from the efficiency ratio for the Hotel and Restaurant tax income in 2009 to 2013 was very efficient. Judging effective ratio Hotel and Restaurant tax income in 2009 to 2013 was very effective
Keywords: Department of Revenue Performance Buleleng, Value For Money, Taxes Hotels and Restaurants